2018
DOI: 10.22159/ajpcr.2018.v11i7.26017
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Benzopyran Derivatives in Pharmacotherapy of Breast Cancer

Abstract: One of the naturally occurring compounds containing oxygen moiety is benzopyran. Depending on its substitution pattern, different biological effects are shown. The benzopyran ring system is present in many natural products (such as genistein, hesperidin, and warfarin) as well as synthetic products. It displays pharmacological properties such as antitumor, anti-HIV, antimicrobials, anti-inflammatory, and anticoagulants. The sufficient literature support and the fact that benzopyran has potential as a pharmacoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Generally, cancer can be measured by assessing the degree of mitochondrial impairment and metabolic dysfunctions such as cellular energy supply, cell death signaling, irregulation of metabolic pathways, formation of reactive oxygen species (ROS), compromised enzyme actions, aerobic glycolysis augmented in tumor cells, alterations in lipid metabolism and unbalanced pH [ 6 ]. Therefore, to cure such metabolic dysfunctions, naturally occurring flavonoids, flavonols, flavanones (2-phenyl chroman-4-one derivatives) and homoisoflavanones exhibit good anticancer potential along with other pharmacological activities such as anti-inflammatory, antioxidative, antidiabetic, antibacterial, antimicrobial, antifungal, antimutagenic, antiparasitic and anti-HIV [ 7 , 8 ]. In this regard, the following naturally occurring flavanones such as naringenin [ 9 ], naringin [ 9 ], sakuranetin [ 10 ], eriodictyol [ 11 ], calyxin G, deguelin [ 12 ] and sterubin [ 13 ] have been reported (Figs.…”
Section: Biological Activities Of Chromanonementioning
confidence: 99%
“…Generally, cancer can be measured by assessing the degree of mitochondrial impairment and metabolic dysfunctions such as cellular energy supply, cell death signaling, irregulation of metabolic pathways, formation of reactive oxygen species (ROS), compromised enzyme actions, aerobic glycolysis augmented in tumor cells, alterations in lipid metabolism and unbalanced pH [ 6 ]. Therefore, to cure such metabolic dysfunctions, naturally occurring flavonoids, flavonols, flavanones (2-phenyl chroman-4-one derivatives) and homoisoflavanones exhibit good anticancer potential along with other pharmacological activities such as anti-inflammatory, antioxidative, antidiabetic, antibacterial, antimicrobial, antifungal, antimutagenic, antiparasitic and anti-HIV [ 7 , 8 ]. In this regard, the following naturally occurring flavanones such as naringenin [ 9 ], naringin [ 9 ], sakuranetin [ 10 ], eriodictyol [ 11 ], calyxin G, deguelin [ 12 ] and sterubin [ 13 ] have been reported (Figs.…”
Section: Biological Activities Of Chromanonementioning
confidence: 99%
“…Nicolaou et al [23] labelled the benzopyran scaffold as a privileged structure because it is found in a range of biologically active compounds, both synthetic and naturally occurring. The benzopyran structural motif plays an important role in numerous pharmaceutical molecules with a wide range of biological properties, which include anti-cancer [24], anti-inflammatory [25], antibacterial [26], anti-arthritis [27], anti-viral [28], anti-Alzheimer's [29], anti-skin disease activities [30] and the treatment of type 2 diabetes [31]. In addition some benzopyran derivatives have demonstrated potential as alanine racemase inhibitors [32], cytochrome P450 1B1 (CYP1B1) inhibitors [33], monocarboxylate transporter 1 inhibitors [34], P-glycoprotein inhibitors [35] and α-glucosaminidase inhibitors [36].…”
Section: Organic and Medicinal Chemistry International Journalmentioning
confidence: 99%
“…For example, regarding the biosynthesis of chromans, they generally involved the (formal) oxa-Diels–Alder reaction between alkenyl-phenols as dienophiles and ortho -quinone methides ( o -QMs) as dienes in situ -generated from the corresponding phenolic compounds. , As illustrated in Figure , the privileged trisubstituted chroman scaffold I featured three contiguous tertiary carbon stereocenters on the highly saturated benzo-dihydropyran motif. It commonly occurred in a number of natural products and biologically active molecules. , Notably, these natural compounds generally existed in the diverse stereostructural forms, which is distinguished from most of the stereospecific natural products. Therefore, it is highly appealing to develop an efficient biomimetic synthetic methodology, exclusively delivering the diverse stereostructural chromans in asymmetric catalysis.…”
Section: Introductionmentioning
confidence: 99%